Effect of Gibberellic Acid and Urea Fertilizer on Some Qualitative and Quantitative Characteristics for Two Celery Cultivars (Apium graveolens L.) - Mehdi I.H.; Alasadi M.J.M. (Al-Qadisiyah Journal of Pure Science, 2018)
An experiment was conducted in the winter season (2013 -2014) A.C. in house garden in the province of Dhi-Qar, to find out effects of gibberellic acid concentrations, level of urea fertilizer and their intraction on some qualitative and quantitative characteristics for two celery cultivars (Apium graveolens L.)Experiment was designed as Randomized Comlete Block Design (RCBD) in a factorial arrangement with three replicates and organized treatments for three factors, first factor included two celery cultivars (local and imported), the second factor included four concentrations of gibberellic acid (0, 50, 100 and 150) mg. L-1 and the third factor included four levels of urea fertilizer (0, 10, 20 and 30) g. Kg-1 soil. Means were compared by using Revised Least Significant Difference (RLSD) at 0.05 probability level.Results showed that gibberellic acid concentrations and levels of urea fertilizer influenced significantly increase leaves content of carbohydrates, nitrogen, phosphorus, potassium and total protein, as well as the percentage of volitle oil in seeds of twice cultivars also increased the qualities of yield celery plant from seed; the results showed superiority of imported cultivar in the majority of the studied characteristics while local cultivar recipes in the leaves content of total chlorophyll and the percentage of oil in the seed. Gibberellic acid concentrations caused a significant increase in all characteristics were significantly increased at the highest concentration of 150 mg. L-1 for most characteristics, while level of urea fertilizer recorded 30g. Kg-1 soil increased higher significantly in the majority of the characteristics.